Complexation Engineering of Electron Transport Layers for High‐Performance Perovskite Solar Cells. Issue 8 (10th August 2022) - Lin, Zhichao; Zhang, Wenqi; Cai, Qingbin; Xu, Xiangning; Dong, Hongye; Mu, Cheng; Zhang, Jian-Ping
Abstract : Perovskite Solar Cells In article number 2200343, Zhichao Lin, Cheng Mu, and co‐workers discovered that the modification of divalent transition metal complexes [Ni(NH3 )6 ]F2 or [Co(NH3 )6 ]F2 optimize the energy level arrangement of SnO2 electron transport layer, passivate the defects of the SnO2 /perovskite interface, and improve the crystallinity of the perovskite layer, thus improving the performance of perovskite solar cells and making their application in space exploration possible.